The research The reality of work stress and its relationship to the performance of administrative tasks among secondary school principals : "A field study in Latakia Governorate" (Journal of Hama University, 2024)
The aim of the current research is to identify the reality of work pressures and their relationship to the performance of administrative tasks among secondary school principals, and to identify the differences in their views on the work pressures they face and the degree of their performance of their administrative tasks according to the variables: number of years of experience, academic and educational qualifications, and school location.  To achieve the research objectives, the researcher built a questionnaire to identify the reality of work stress, which consisted of (19) statements, and a questionnaire to investigate the degree to which secondary school principals practice their administrative tasks, which consisted of (21) statements. To verify the validity of the questionnaire, it was presented to (5) specialized educational arbitrators, and reliability was calculated using the split-half method. It was distributed to a sample of (72) male and female principal and the researcher used the descriptive approach to suit the research topic.  The results of the research showed that the reality of work stress among secondary school principals from their point of view and the degree of their practice of their administrative tasks was of a moderate degree. There were apparent differences between the principals’ answers to both the work stress questionnaire and the administrative tasks questionnaire due to the variables “number of years of experience, academic qualification, and location.” The results showed that there is a correlation between the work pressures experienced by secondary school principals and their performance of the administrative tasks required of them. Based on the results, the researcher presented improving the administrative work environment in secondary schools by providing training programs for principals that reduce workloads.